Isolation, purification and characterization of vinblastine and vincristine from endophytic fungus fusarium oxysporum isolated from catharanthus roseus - Kumar, Ashutosh; Patil, Deepak; Rajamohanan, Pattuparambil Ramanpillai; Ahmad, Absar (Plos One, 2013)
Endophytic fungi reside in a symbiotic fashion inside their host plants, mimic their chemistry and interestingly, produce the same natural products as their hosts and are thus being screened for the production of valuable compounds like taxol, camptothecin, podophyllotoxin, etc. Vinblastine and vincristine are excellent anti-cancer drugs but their current production using plants is non-abundant and expensive. In order to make these drugs readily available to the patients at affordable prices, we isolated the endophytic fungi from Catharanthus roseus plant and found a fungus AA-CRL-6 which produces vinblastine and vincristine in appreciable amounts. These drugs were purified by TLC and HPLC and characterized using UV-Vis spectroscopy, ESI-MS, MS/MS and H-1 NMR. One liter of culture filtrate yielded 76 mu g and 67 mu g of vinblastine and vincristine respectively. This endophytic fungal strain was identified as Fusarium oxysporum based upon its cultural and morphological characteristics and internal transcribed spacer (ITS) sequence analysis.